2011
DOI: 10.1002/ardp.201000363
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Tandem Aza‐Wittig Reaction to Synthesize Artemisinin–Guanidine Hybrids and Their Anti‐Tumor Activity

Abstract: Three series of novel artemisinin-guanidine hybrids 4a-4f, 8a-8h and 9a-9h have been facilely synthesized via four-component reaction (aza-Wittig reaction) and evaluated for their anti-tumor activities against A549, HT-29 and MDA-MB-231 cell lines in vitro. All of the tested compounds showed enhanced anti-tumor activities with IC(50) values ranging from 0.02 µM to 12.0 µM as compared to DHA (dihydroartemisinin). Among them, artemisinin derived dimers, compounds 9b (IC(50)  = 0.05 µM), 9d (IC(50)  = 0.06 µM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The IC 50 s on human HT-29 colon and HeLa cervical cancer cells were between 0.12 and 0.85 μM. Xie et al [123] have also synthesized artemisinin-guanidine hybrids. The Guanidine moiety would make the molecule more water soluble.…”
Section: Lai Andmentioning
confidence: 96%
See 1 more Smart Citation
“…The IC 50 s on human HT-29 colon and HeLa cervical cancer cells were between 0.12 and 0.85 μM. Xie et al [123] have also synthesized artemisinin-guanidine hybrids. The Guanidine moiety would make the molecule more water soluble.…”
Section: Lai Andmentioning
confidence: 96%
“…Deoxoartemisinin trimers are even more potent than pacilitaxel, 5-fluorouracil, and cisplatin on oral cancer cells. The artemisinin-guanidine dimers of Xie et al [123] are more potent than its monomer and have IC 50 s of 20-60 nM against HT-29 human colon cancer cells. The highly selective cytotoxicity of artemisinin dimers towards cancer cells makes them an attractive option for development for cancer treatment.…”
Section: Artemisinin Dimers and Trimersmentioning
confidence: 98%
“…This hybrid dimer showed up to 600-fold more potent cytotoxicity than DHA ( 2 ) toward the human A549 non-small-cell lung adenocarcinoma, HT-29 colon cancer, and MDA-MB-231 breast cancer cell lines [61]. Recently, three artesunic acid homodimers have been synthesized and evaluated for their activity against human CCRF-CEM and MDR P-glycoprotein-overexpressing CEM/ADR 5000 leukemia cells, and the MDR cells used were found not to be cross-resistant to these new dimers [62].…”
Section: Artemisinin Dimers Showing Improved Antitumer Potentialmentioning
confidence: 99%
“…Dimer 22a (IC 50 : 680 nM) showed cytotoxicity towards CHO cells, whereas compound 22b (IC 50 : 74,820 nM) displayed low cytotoxicity. The guanidine‐containing dimers 23 (IC 50 : 0.02–2.08 μM, MTT assay) demonstrated considerable activity against A549, HT‐29, and MDA‐MB‐231 cancer cell lines, and all of them were more potent than dihydroartemisinin (IC 50 : 7.8–12.0 μM) . The SAR revealed that all guanidine‐containing dimers were more active than the corresponding monomers, whereas the chalcone‐containing dimers were less potent than the corresponding monomers .…”
Section: Ether‐tethered Artemisinin‐derived Dimersmentioning
confidence: 99%
“…The guanidine‐containing dimers 23 (IC 50 : 0.02–2.08 μM, MTT assay) demonstrated considerable activity against A549, HT‐29, and MDA‐MB‐231 cancer cell lines, and all of them were more potent than dihydroartemisinin (IC 50 : 7.8–12.0 μM) . The SAR revealed that all guanidine‐containing dimers were more active than the corresponding monomers, whereas the chalcone‐containing dimers were less potent than the corresponding monomers . Moreover, the bis‐substituted dimer 23a (IC 50 : 0.02–1.42 μM) was generally more potent than the monosubstituted analogs against A549, HT‐29, and MDA‐MB‐231 cancer cell lines.…”
Section: Ether‐tethered Artemisinin‐derived Dimersmentioning
confidence: 99%